PENGARUH PENGGUNAAN PUPUK CAIR HASIL FERMENTASI LIMBAH CAIR INDUSTRI PENGOLAHAN KARET TERHADAP KETERSEDIAAN CA, MG DAN SO 4= - Sofia Anita; Itnawita Itnawita (Jurnal Ilmu Lingkungan, 2014)
Crumb rubber wastewater fermented using Effective Microorganisms (EM) was rich inmicroorganisms and nutrients such as proteins, carbohydrates, fats, and other organiccompounds. Therefore, it is possible as liquid fertilizer. The purpose of this study are toanalyse the nutritional contents (calcium, magnesium, sulphate) in term of variationtime of watery (1x1 day, 1x2 days dan 1x3 days) and fermentation (1,2, and 3 months).The variation time of watery and fermentation shows the increasing of nutrientssignificantly. The present of magnesium and sulphate on the watery everyday and 2months fermented shows significant different of 154,47 mg /g and 29,65 mg/g,respectively. Otherwise, calcium shows significant different within 2 days watery and 1month fermented of 30,10 mg/g